2012
DOI: 10.1002/aenm.201200219
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of the P3HT/PCBM Solar Cells through NIR Sensitization Using a Small‐Bandgap Polymer

Abstract: A smart strategy to significantly improve the energy conversion efficiency of the wide‐bandgap polymer P3HT blended in PCBM is demonstrated through NIR sensitization with a low‐bandgap polymer. An efficiency of over 4% is achieved by adding 30–40% of the low bandgap polymer Si‐PCPDTBT to the binary P3HT:PCBM blend, corresponding to an efficiency improvement of 25% compared to the P3HT:PCBM reference binary blend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
182
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(189 citation statements)
references
References 21 publications
7
182
0
Order By: Relevance
“…We also tried to discover whether there might be a characteristic length of the side chains at which the electronic properties would remain unchanged; this might be suitable for use as a modeling approach. We chose to study poly(3-hexylthiophene) (P3HT), a polymer widely used in organic devices (Figure 1) [8][9][10][20][21][22][23][24] . This polymer has a hexyl side chain in each monomer unit.…”
Section: Introductionmentioning
confidence: 99%
“…We also tried to discover whether there might be a characteristic length of the side chains at which the electronic properties would remain unchanged; this might be suitable for use as a modeling approach. We chose to study poly(3-hexylthiophene) (P3HT), a polymer widely used in organic devices (Figure 1) [8][9][10][20][21][22][23][24] . This polymer has a hexyl side chain in each monomer unit.…”
Section: Introductionmentioning
confidence: 99%
“…Various sensitizers based on low band gap polymers [55][56][57][58][59][60][61][62][63], small molecules [64][65][66], dyes [67][68][69] and nanoparticles [13][14][15][16][17][18][19][20][21] are employed in the structure of the photoactive layer in combination with donor material which is usually consists of a large bandgap polymer and fullerene derivative as acceptor. Recently, the record PCEs over 12% have been reported for the PBDB-T:IT-M: BisPC 70 BM (1:1:0.2) ternary solar cells with a Jsc=17.3 mA/cm², Voc=0.95 V and FF=74% [42], which demonstrate the potential of ternary sensitization concept for OPVs' upscaling.…”
Section: Ternary Solar Cellsmentioning
confidence: 99%
“…Han et al [100] added 5 wt% InP QDs into the PTB7:PC 71 BM host matrix and reported a maximum PCE of 8.4% for the ternary device due to the increase in J SC and FF by the synergy effect of InP QDs and the used Poly [(9,9-bis(3'-(N,N-dimethylamino)propyl)-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene)] (PFN) interlayer. In 2016 our research group fabricated hybrid solar cells based on pDPP5T-2 electron donating polymer, PC 61 BM and cadmium selenide telluride (CdSe X Te 1-X ) QDs and evaluated the photovoltaic performance and optoelectronic properties of the prepared devices as a function of QDs loading. The power conversion efficiency of the fabricated hybrid solar cells was improved up to 5.11% for the device containing 4 wt% of CdSe X Te 1-X QDs which found to be mainly due to the enhancement in short circuit current density resulted from the enlarged light harvesting potential of the photoactive layer [17].…”
Section: Hybrid Qd Based Solar Cellsmentioning
confidence: 99%
“…A thermal annealing method has been proposed for crystalline polymerbased BHJ systems [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] , while an additive method is currently used for less-crystalline (amorphous) polymer-based BHJ layers [37][38][39][40][41][42][43][44][45][46][47] . However, it is doubtable that such an optimized BHJ layer (system) can withstand external physical loads such as pressing, hitting, rubbing and the like when it comes to the fullerene nano-domains dispersed in the polymer:fullerene mixture structures.…”
Section: Introductionmentioning
confidence: 99%